Ordination and Disrobing in Theravada Buddhism: The Sangha as a Barometer of the Community - Crosby, Kate (Religions of South Asia, 2014)
Much has been written about motivations for becoming a monk in Theravada societies. This article examines the other end of the process, the monk’s ‘re-entering’ society. It begins by looking at the motives for becoming a monk, and the difference between the lifelong commitment typical of Sri Lanka and the temporary ordination typical of Southeast Asian countries. It then looks at motives for disrobing, which may be a wish to enjoy lay life, a wish to serve one’s family or the community, a sense of unworthiness, or dissatisfaction with the Sangha. The social and economic problems faced by the former monk are also discussed. We then look at what disrobing practices tell us about the position of Theravada and of the Theravada monk in different Southeast Asian countries.